GNOMES II: Analysis of the Galactic diffuse molecular ISM in all four ground state hydroxyl transitions using Amoeba. (28th February 2023) - Petzler, Anita; Dawson, J. R.; Nguyen, Hiep; Heiles, Carl; Wardle, M.; Lee, M.-Y.; Murray, Claire E.; Thompson, K. L.; Stanimirović, Snežana
Abstract: We present observations of the four $^2 Π _{3/2}\, J=3/2$ ground-rotational state transitions of the hydroxyl molecule (OH) along 107 lines of sight both in and out of the Galactic plane: 92 sets of observations from the Arecibo telescope and 15 sets of observations from the Australia Telescope Compact Array (ATCA). Our Arecibo observations included off-source pointings, allowing us to measure excitation temperature ( $T_{\rm ex}$ ) and optical depth, while our ATCA observations give optical depth only. We perform Gaussian decomposition using the Automated Molecular Excitation Bayesian line-fitting Algorithm 'Amoeba ' (Petzler, Dawson, & Wardle 2021, ApJ, 923, 261) fitting all four transitions simultaneously with shared centroid velocity and width. We identify 109 features across 38 sightlines (including 58 detections along 27 sightlines with excitation temperature measurements). While the main lines at 1665 and 1667 MHz tend to have similar excitation temperatures (median $|Δ T_{\rm ex}({\rm main})|=0.6\, $ K, 84% show $|Δ T_{\rm ex}({\rm main})|<2\, $ K), large differences in the 1612 and 1720 MHz satellite line excitation temperatures show that the gas is generally not in LTE. For a selection of sightlines, we compare our OH features to associated (on-sky and in velocity) Hi cold gas components (CNM) identified by Nguyen et al. (2019, ApJ, 880, 141) and find no strong correlations. We speculate that this may indicate an effective decoupling of the molecular gas from the CNM once it accumulates.